2013
DOI: 10.1002/jmri.24290
|View full text |Cite
|
Sign up to set email alerts
|

Rapid multicomponent T2 analysis of the articular cartilage of the human knee joint at 3.0T

Abstract: Multicomponent T2 parameters of the articular cartilage of the human knee joint can be measured at 3.0T using mcDESPOT and show depth-dependent and regional-dependent variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 52 publications
3
73
0
Order By: Relevance
“…These results will be of significance for high resolution whole-brain MWF mapping. Further, BMC-mcDESPOT can readily be extended to incorporate exchange between pools and to other tissues, including, for example, the estimation of the proteoglycan-associated water fraction in cartilage (58-59). …”
Section: Discussionmentioning
confidence: 99%
“…These results will be of significance for high resolution whole-brain MWF mapping. Further, BMC-mcDESPOT can readily be extended to incorporate exchange between pools and to other tissues, including, for example, the estimation of the proteoglycan-associated water fraction in cartilage (58-59). …”
Section: Discussionmentioning
confidence: 99%
“…short imaging time, which makes it feasible for use in clinical practice and osteoarthritis research studies (35). Authors of few previous studies have investigated multicomponent T2 parameters in human articular cartilage.…”
Section: Musculoskeletal Imaging: Articular Cartilage Of the Human Knmentioning
confidence: 99%
“…Single-component T2 (T2 Single ) maps were created by using the driven equilibrium singleshot observation of T2 full-modeling reconstruction method (33). Results of previous studies have shown high pixelby-pixel correlation between cartilage T2 Single measurements obtained by using mcDESPOT and those obtained by using conventional Carr-Purcell-Meiboom-Gill techniques (35). Multicomponent T2 maps for the fast-relaxing water component (T2 F ) and the slow-relaxing water component (T2 S ) and maps for the fraction of the fast-relaxing water component (F F ) were created by using the two-pool mcDESPOT reconstruction method (29)(30)(31).…”
Section: Implication For Patient Carementioning
confidence: 99%
“…However, changes in T2 and T2* are nonspecific and can be caused by multiple factors including hydration, macromolecular content, and tissue anisotropy with comparable changes occurring in disparate settings [5][6][7][8][9] . Bi-component T2 and T2* mapping techniques have been used to improve the specificity of T2 analysis by assessing the individual water components of musculoskeletal tissues [10][11][12][13][14][15][16][17][18][19][20][21][22] . Bi-component T2 and T2* mapping methods have measured two distinct T2 components in cartilage assumed to represent short relaxing water bound to the macromolecular matrix and long relaxing bulk water [12][13][14]21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Bi-component T2 and T2* mapping techniques have been used to improve the specificity of T2 analysis by assessing the individual water components of musculoskeletal tissues [10][11][12][13][14][15][16][17][18][19][20][21][22] . Bi-component T2 and T2* mapping methods have measured two distinct T2 components in cartilage assumed to represent short relaxing water bound to the macromolecular matrix and long relaxing bulk water [12][13][14]21,22 . Bi-component T2* mapping methods have been used in cortical bone to differentiate between water bound to the organic matrix and free water in the Haversian systems [15][16][17] , Bi-component T2 and T2* mapping methods have also been used in the meniscus to differentiate between macromolecular bound water and bulk water [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%